Implementation of Regents Regulations on Compulsory Madrasah Diniyah Learning in the Development of MDT Institutions. Riyadhul Jinan Pasuruan - Faishol Ahmad; Renny Oktavia; Taufiq Churrohman (International Consortium of Education and Culture Research Studies, 2020)
Before the enactment of the Pasuruan Regent Regulation no. 21 of 2016 concerning Compulsory Education for Madrasah Diniyah, there has been a Regional Regulation of Pasuruan Regency Number 4 of 2014 concerning the Implementation of Education which one of the contents in article 31 paragraph 2 describes the mandatory madrasah diniyah in Pasuruan. This regulation was made and determined by Mr. HM. Irsyad Yusuf, SE as the elected Regent of Pasuruan, because there is encouragement to restore the icon of Pasuruan Regency as Santri City and instill religious values in students. After 3 years this Perbup was running, it turned out to have a positive effect and impact on the Pasuruan community moreover to 1,439 Madin institutions that already existed included MDT. Riyadhul Jinan, located in Kedungboto Village, Kec. Beji Pasuruan Regency. In the second period after being re-elected as Regent, he had a superior program namely